Pharmacotherapeutics In Prosthodontics – An Overview - Singh, Dr. Gaurav Pal; Soni, Dr. Vishnu Kumar; Teena, Dr; Nehra, Dr Saroj (Asian Journal of Pharmaceutical Research and Development, 2021)
Pharmacology is the science of drugs. Drug is the single active chemical entity present in a medicine that is used for diagnosis, prevention, treatment of a disease. Pharmacology deals with interaction of exogenously administered chemical molecules (drugs) with living systems. The two main aspects of concern are the effects of drugs on biological systems and the effect of biological systems on efficacy and metabolism of drugs. Drugs play an important role in improving the response of the patient in both pre-treatment and post-treatment phases. Drugs in dentistry act as a primary treatment modality as well as facilitator of dental procedures. With phenomenal growth of information on the mechanism of action and clinical application of drugs as well as rapid introduction of new drugs, pharmacology has become increasingly important to all dentists. Prosthodontics is that specialty of dentistry which deals with patients of all ages, hence making it more important to know about the local and systemic effects of drugs and their side effects.